BMP4 increases expression of HMGA2 in mesenchymal stem cells - Markowski, Dominique Nadine; Helmke, Burkhard Maria; Meyer, Frauke; von Ahsen, Inga; Nimzyk, Rolf; Nolte, Ingo; Bullerdiek, Jörn (Cytokine, 2011)
BMP4 has been linked to early steps of adipocyte lineage differentiation but only little is known about its corresponding downstream pathways. Herein, we have investigated whether or not the expression of high mobility group protein HMGA2, another protein linked to proliferation and differentiation within the process of adipogenesis, may be influenced by BMP4 signaling in adipose tissue derived stem cells. Compared to FGF1, a strong inducer of HMGA2 in immortalized pre-adipocytes, BMP4 was found moderately to induce the HMGA2 mRNA expression in serum starved adipose tissue derived stem cells and myometrial cells. In contrast, no such activity was noted in canine bone marrow derived mesenchymal stem cells. As to adipocyte lineage differentiation the functions of BMP4 and HMGA2 mechanistically overlap. Thus, we propose that in adipose tissue BMP4 acts in part by activating HMGA2 making this architectural transcription factor one of the major downstream players in that system.
Gesehen am 10.08.2022